Ileal Ischaemic Necrosis due to Metastatic Mesenteric Carcinoid - B R yelikar; K mamatha; Namrata Balachandra Mestri; Deepthi Chandrika Chintalapudi; Anil Reddy Kondurudi (Journal of Clinical and Diagnostic Research, 2019)
Carcinoid tumours are the rare tumours arising from neuroendocrine cells. These tumours are relatively slow growing and may be clinically apparent only after a metastatic spread or evidence of Carcinoid syndrome. Rarely, these tumours may cause ischaemic necrosis in the non-neoplastic small intestine due to elastic vascular sclerosis of the mesenteric vessels. Here, authors present a case of metastatic mesenteric Carcinoid associated with ischaemic necrosis of the ileum.